Optical characterisation of nanowire lasers. (August 2022) - Church, Stephen A.; Al-Abri, Ruqaiya; Parkinson, Patrick; Saxena, Dhruv
Abstract: Semiconductor nanowire lasers are single-element structures that can act as both gain material and cavity for optical lasing. They have typical dimensions on the order of an optical wavelength in diameter and several micrometres in length, presenting unique challenges for testing and characterisation. Optical microscopy and spectroscopy are powerful tools used to study nanowire lasers; here, we review the common techniques and analytical approaches often used and outline potential pitfalls in their application. We aim to outline best practise and experimental approaches used for characterisation of the material, cavity and lasing performance of nanowires towards applications in biology, photonics and telecommunications.